Analysis of the Financial Performance of the Regional Government of East Lombok Regency Using the Value for Money Approach for the 2017-2021 Fiscal Year - Husnul Riati; Abdul Manan; Eka Agustiani (LPPM Institut Studi Islam Sunan Doe, 2024)
This study aims to determine the financial performance of the East Lombok Regency Government as measured using the Value for Money approach which consists of economy, efficiency, and effectiveness, and to determine whether the financial performance calculated using the Value for Money approach is in accordance with Kemendagri No. 600900-327 in 1996. This research was conducted at the Regional Financial and Asset Management Agency (BPKAD) of East Lombok Regency. The results of the study show that the financial performance of the East Lombok Regency government with a value for money approach is as follows: the financial performance of the East Lombok Regency government from 2017-2021 with economic indicators shows that the economic ratio is between economic criteria (90-100%). This means that the government has been less successful in controlling the costs incurred resulting in wasteful and unproductive spending.,The financial performance of the East Lombok Regency government from 2017-2021. with efficient indicators, the performance of the Regional Government of East Lombok Regency is less efficient because the ratio shows results of 90-100%.